Eficacia de protocolos de manejo del dolor postoperatorio en cirugía abdominal mayor en el Hospital Regional de Loreto, 2026 - Zegarra Davila, Roberto Carlos (2026)
Introduction: Postoperative pain following major abdominal surgery is associated with a high symptom burden and intensive opioid use, with repercussions on complications, hospital stay, and functional recovery. Multimodal analgesia, based on a combination of non-opioid drugs and regional techniques, is proposed as an alternative to modulate nociceptive pathways and reduce the requirement for opioids. Objective: To evaluate the efficacy of postoperative pain management protocols in major abdominal surgery at the Loreto Regional Hospital, 2026. Method: This will be an experimental study, and a randomized controlled trial (RCT) will be conducted to evaluate the efficacy of different postoperative pain management protocols. The study will be analytical, longitudinal, and prospective, with serial measurements of pain and clinical outcomes up to 72 hours. Population: The population will include adult patients undergoing major abdominal surgery at the Loreto Regional Hospital. A sample of 175 participants who meet predefined inclusion and exclusion criteria will be selected using simple random probability sampling and randomly assigned to protocols based on multimodal analgesia or opioids. Results: A refined and coded database will be created. Descriptive statistics will be applied to characterize clinical variables, pain intensity (VAS), opioid consumption, adverse effects, length of stay, and satisfaction. Comparisons between protocols will be made using Student's t-test, χ² statistics, and analysis of variance; additionally, multiple regression models will be adjusted to control for confounding variables, with a significance level of p<0.05 using SPSS version 26 or higher. Conclusion: The findings will allow us to define the comparative performance of multimodal analgesia versus opioid centered regimens in major abdominal surgery, generating criteria for adjusting institutional protocols and rationalizing the use of opioids in the perioperative period.